Pushing the limits: ship rat (Rattus rattus) population dynamics across an elevational gradient in response to mast seeding and supplementary feeding - Joanna K. Carpenter; Adrian Monks; John Innes; James Griffiths (Biological Invasions, 2022)
Understanding marginal habitat use by invasive species is important for predicting how distributions may change under future climates. We investigated the influence of food availability and temperature on ship rat ( Rattus rattus ) distribution and density across a forested elevational gradient in New Zealand by measuring ship rat demographics following a beech (Nothofagaceae) mass seeding event (‘mast’) at three elevation bands (20–80, 400–500, 800–900 m asl). We tested whether declining food availability limits rat populations at the highest elevation band post-mast by experimentally increasing food abundance above baseline food availability. When our study started 4 months post-seedfall, rats at mid- and low- elevations were at high densities (11.4–16.5 ha −1 ). Rats at higher elevations were barely detectable, but densities peaked (9.4 ha −1 ) 10 months post-seedfall, with the initial increase possibly driven by immigration from lower elevations. All populations declined sharply over the next year. Supplementary feeding at high elevation increased survival, recruitment, and density of rats through winter, 16 months post-seedfall, relative to unfed grids, suggesting food limitation. However, both fed and non-fed populations declined to zero by the following spring, perhaps due to stoat ( Mustela erminea ) predation. Our results suggest that low food availability plays a significant role in restricting rats from cool, high elevation environments. The variation in the timing and magnitude of ship rat responses to the pulsed resource across the gradient also highlights the importance of initial population size and spatial processes as factors modulating ship rat responses to pulsed resources across a landscape.